1990
DOI: 10.1172/jci114474
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of intranephronal proteinaceous cast formation by low molecular weight proteins.

Abstract: Proteinaceous cast formation in the distal nephron of the kidney from low molecular weight proteinuria is a significant, but poorly characterized, cause of renal failure. To study this phenomenon, we: (a) microperfused the loop segment (LS) of rats in vivo with artificial tubule fluid (ATF) containing four different low molecular weight proteins, 0.01-50 mg/ml, to detect alterations in LS function, and (b) examined the interaction between several proteins and Tamm

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
81
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(86 citation statements)
references
References 34 publications
4
81
1
Order By: Relevance
“…Hemodynamics and intravascular volume should be optimized in an effort to ensure adequate urine output. Oliguric patients may benefit from a trial of volume repletion but should not receive loop diuretics, because they may contribute to paraprotein cast formation (54). Alkalinization of the urine is of uncertain benefit and can theoretically raise the risk of abnormal calcification in the kidney or elsewhere, particularly if hypercalcemia is present.…”
Section: Management Of Aki From Paraprotein-mediated Diseasementioning
confidence: 99%
“…Hemodynamics and intravascular volume should be optimized in an effort to ensure adequate urine output. Oliguric patients may benefit from a trial of volume repletion but should not receive loop diuretics, because they may contribute to paraprotein cast formation (54). Alkalinization of the urine is of uncertain benefit and can theoretically raise the risk of abnormal calcification in the kidney or elsewhere, particularly if hypercalcemia is present.…”
Section: Management Of Aki From Paraprotein-mediated Diseasementioning
confidence: 99%
“…[11][12][13] Factors such as dehydration, hypercalcemia, acidosis and furosemide promote light chain/Tamm-Horsfall protein aggregate formation. [13][14][15][16] Tubular obstruction increases intraluminal pressure, reduces glomerular filtration rate and reduces interstitial blood flow, thus further compromising the renal function. The reduced tubular clearance of light chains further increases their concentration in the tubules and contributes to the vicious circle that results in myeloma cast nephropathy.…”
Section: Pathogenesismentioning
confidence: 99%
“…In general, the variable region of the light chain determines nephrotoxicity of the specific light chain by determining, for example, the affinity with Tamm-Horsfall protein. 14,16 It has been suggested that Tamm-Horsfall protein interacts with the hypervariable regions of the light chains. This region contains the amino acids that give diversity, conformation flexibility and allow for interactions with various proteins to promote antigen binding by immunoglobulins.…”
Section: Pathogenesismentioning
confidence: 99%
“…14 This leads to a greatly increased burden of light chain on PTECs and saturation of the megalin-cubilin pathway, 6,8,9 allowing light chain to travel to the distal nephron where they may interact with Tamm-Horsfall protein and appear in the urine. [15][16][17] There is a mounting body of evidence pointing to exposure of PTECs to excess filtered proteins, resulting in cytokine release, recruitment of inflammatory cells, and the acceleration of interstitial fibrosis. 18 Light chains have been shown to cause nuclear translocation of Nuclear Factor kappa-light-chain-enhancer of activated B cells (NF-B), resulting in the release of interleukin-6 (IL-6), IL-8, monocyte chemoattractant protein-1 (MCP-1), and transforming growth factor-␤ (TGF-␤), and are much more potent inducers of these cytokines than other proteins, such as albumin, which may be filtered and enter the proximal tubule in significant amounts, especially in glomerular disease states.…”
mentioning
confidence: 99%